2005
DOI: 10.12693/aphyspola.107.207
|View full text |Cite
|
Sign up to set email alerts
|

High Pulsed Magnetic Field Sensor Based on La-Ca-Mn-O Thin Polycrystalline Films

Abstract: It is demonstrated that polycrystalline La 0.33 Ca 0.67 MnO 3 thin film sensors can be used to measure pulsed strong magnetic fields with microsecond duration rise and decay times. The response characteristics of these sensors were investigated using 0.7-1.0 ms duration bell-shaped magnetic field pulses of 10-20 T amplitudes and by using special waveform magnetic field pulses with amplitudes of 40 T and decay times of 50 µs. The response of these magnetic field sensors was compared with those of conventional l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In recent years, the discovery of the colossal magnetoresistance in manganite materials has led to the development of the so-called CMR-B-scalar sensor [13], [14]. This sensor type is very small and can be used to measure the absolute value of pulsed magnetic flux densities up to 40 T. An array of such sensors was successfully used to investigate the current distribution in the rails of a railgun by measuring the magnetic field distribution in the vicinity of the rail [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the discovery of the colossal magnetoresistance in manganite materials has led to the development of the so-called CMR-B-scalar sensor [13], [14]. This sensor type is very small and can be used to measure the absolute value of pulsed magnetic flux densities up to 40 T. An array of such sensors was successfully used to investigate the current distribution in the rails of a railgun by measuring the magnetic field distribution in the vicinity of the rail [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients k 1 and k 2 calculated using data from Fig. 2b was 11.34 and 0.625 mV/T, respectively, that give f max ≈ 1.5 kHz according to (1). The f max can be increased biasing sensor by higher voltage, however this way has a limitation due to Joule's heating dissipated in magnetic material.…”
Section: "Loop" Effectmentioning
confidence: 95%
“…It was demonstrated that the colossal magnetoresistance (CMR)-B-scalar sensor can be successfully used for high pulsed magnetic field measurements [1,2]. The sensor is a two-terminal device with thin manganite film as material sensitive to magnetic flux density (B) magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The CMR is a result of the magnetic ordering of the material on the microscopic level and, in general, is sensitive to the magnitude of the magnetic field. However, it was found that the 0018-9464/$25.00 © 2009 IEEE CMR effect in epitaxial manganite films saturates in intermediate magnetic fields (10-15 T) [8] while the magnetoresistance of polycrystalline manganites has no tendency of saturation [9], [10] up to 50 T. Furthermore, the anisotropy of magnetoresistance and hysteresis are observed in epitaxial manganite films while magnetoresistance of polycrystalline films grown at certain conditions is independent of the direction of the magnetic field [11]. These advantages of polycrystalline films were used to design magnetic-field sensors for measuring the magnitude of magnetic fields (B-scalar sensors) independently on their direction.…”
Section: Preparation Of the Cmr-based Sensormentioning
confidence: 99%